Course Content Application: A Case of Principles of Statistics - Jassim, Thamir Naeem (2010)
The electronic learning environment is defining that system use modem ICT technology to support an academic education effort. This project discusses the content development of Principles of Statistics. The main problem that face the students with the current learning system for the Principles of Statistics course, are the inability to communicate with a lecturer because of size class, and lack of appropriate educational tools. Current tools used in the educational process are books and power point slides. Therefore, the student's potential cannot be filly utilized without the current modern tools to increase their capacity in the learning. The main objective of the project is to identify the requirements for web-based system to learn Principles of Statistics (PSS) Course. The general methodology used in this study and the Rational Unified Process (RUB). The proposed web application has been tested based on the usability, the UUM students' acceptance for using this system, which was (Mean = 4.30) by students.